THE IMPROVING CALCULATION OF FLEXURAL-TORSIONAL VIBRATIONS OF CONTINUOUS BEAMS AND FRAMES - Raspopov, O. S. (Science and Transport Progress, 2007)
The suitability logic models and associable matrixes to calculation flexural-torsion oscillations of continuous beam with distribution parameters are researched. The inferential matrixes to consider various combination of elastic constraints and given localized masses.